Wrinkle defects investigation on displacement response in fiber-reinforced composites using grating projection measurement. (1st October 2022) - Wen, Ange; Ma, Li; Shen, Chuanchuan; Guo, Jing; Zheng, Jinyang
Abstract: Wrinkle defects in fiber-reinforced polymer (FRP) composites are often unavoidable due to various causes during the production process, which are also difficult to be rapidly screened by conventional non-destructive testing (NDT) methods. In order to find defects in FRP within non-destructive status, a three-dimensional (3D) finite element analysis (FEA) containing micro mechanical model of wrinkle has been applied to predict the mechanical responses in elastic range. It is found that displacement responses under certain loads are noticeably distorted by wrinkle, especially out-of-plane displacement under tension, which provides a defect inspection guidance for FRP. Therefore, a novel wrinkle defect detection method for FRP based on grating projection measurement is proposed. Combined with the measured point clouds and surface reconstruction algorithm, the full-field out-of-plane displacement distortion of 10 μm measuring precision can be obtained. Tensile tests with a small force are carried out to ensure the wrinkled FRP specimens in the elastic range, the obtained out-of-plane displacement field satisfactorily reflect the wrinkle-induced disturbances. And the measured out-of-plane displacement using grating projection are in good agreement with the predicted responses from numerical approaches.